In Vitro Regeneration Of Brinjal (Solanum Melongena L.) (Bangladesh Journal of Agricultural Research, 2011)
The effect of different explants and concentrations of BAP and NAA on induction of callus and plant regeneration of brinjal cv. Jhumki were investigated. The treatment combinations were BAP (0. 2.0. 3.0, and 4.0 mg/l) and NAA (0. 0.1, 0.5, and 1.0 mg/l). The rate of callus formation varied in different treatments. The highest amount of callus (48.66%) was produced on MS medium containing 2.0 mg/l BAP and 0.5 mg/l NAA from stem, and 8.2 days required for callus induction. The highest fresh weight of callus was 1.12g from stem and 0.48g from root. The number of shoot regenerated through callus from stem containing 2.0 mg/l BAP and 0.5 mg/l NAA was 3.4 (23.287%) and days required for 38.8 days. All regenerated plantlets survived in normal environment. Keywords: NAA; BAP; regeneration; brinjal. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9268 BJAR 2011; 36(3): 397-406